Overactive bladder and urgency urinary incontinence in men undergoing artificial urinary sphincter placement. Issue 5 (27th April 2020) - Jahromi, Mona S.; Engle, Kyrra; Furlong, Daniel; Guevara Méndez, Alejandra; Gomez, Christopher S.
Abstract: Purpose: To assess persistent and de novo rates of overactive bladder (OAB) and urgency urinary incontinence (UUI) in patients with incontinence after prostate treatment (IPT) focusing on differences between surgical intervention vs radiation. Methods: We performed a retrospective review of 79 patients who underwent primary artificial urinary sphincter (AUS) placement and activation from a single surgeon between February 2012 and November 2017. Four patients with neurogenic bladder were excluded and two with insufficient follow‐up. The primary outcome measures were persistent OAB, persistent UUI, and pad usage before and after AUS placement. Results: After activation of the AUS, 67% of non‐radiated patients had resolution of urgency incontinence vs only 31% of the radiated patients ( P = .096). After activation of the AUS, resolution of OAB symptoms was more common in the non‐radiated group. We found 53% of the non‐radiated group vs only 22% of the radiated group had resolution of their urinary urgency ( P = .045). Previous history of radiation was a risk factor for OAB after implantation of AUS (odds ratio [OR], 3.63; P = .010). Postoperative oral medical pharmacotherapy for OAB was higher in those with previous radiation vs those without prior radiation (66.7% vs 25.7%, P = .001). A history of OAB or UUI did not affect social continence after AUS placement. Conclusion: Radiation is a risk for continued OAB after AUS activation. Appropriate counseling is necessary pre‐ and postoperatively to manage patient expectations and provide additional medical therapies. Mixed urinary incontinence or OAB symptoms should not exclude patients from undergoing AUS placement.